Development of the Heater for Flat Panel Display Manufacturing Process using Control Zone Reduction and Self-Temperature Compensating Technology - Park, Hyoung-Keun (International Journal of Engineering and Technology, 2019)
Conventional control technology of far infrared ray heater does not apply the rule of heater map (heater combination) according to the enlargement of glass due to weak pattern design technology of heater, and it is arbitrarily combined with designers or customers according to the tendency and demands. That is, the heater pattern designer and the technical skill of the customer can cope with the division of the general control zone number without considering the correction ability according to the heat sink amount. In this study, by using the patterning technology of the heater using the surface Temperature Coefficient of Resistance (TCR) of the heater, the technology capable of dramatically reducing the number of control zones is obtained by securing the design ability to perform the temperature correction by itself. In addition, since the Argent-Palladium (Ag-Pd) of the resistor has a TCR characteristic about 10 times that of the nichrome, the self-temperature correction is performed in the heater plate by effectively patterning the resistor of the high TCR. Therefore, we developed a hot plate oven using a steel heater as a solution to solve the problems of the glass curing device which is indispensable for the Liquid Crystal Display (LCD) and Organic Light Emitting Diode (OLED) manufacturing process and satisfy the needs of the customer.